How do you simplify #(g^0h^7j^-2)/(g^-5h^0j^-2)#?

1 Answer
Mar 2, 2017

Answer:

See the entire simplification process below:

Explanation:

The first step I would take is to rewrite this expression as:

#(g^0/g^-5)(h^7/h^0)(j^-2/j^-2)#

We can use this rule of exponents to simplify this expression:

#a^color(red)(0) = 1#

And, we know #x/x = 1# therefore #J^-2/j^-2 = 1#

So we can again rewrite the expression as:

#(1/g^-5)(h^7/1)(1) = h^7/g^-5#

We can eliminate the negative exponent by using this rule for exponents: #1/x^color(red)(a) = x^color(red)(-a)#

#h^7/(g^color(red)(-5)) = h^7g^color(red)(- -5) = h^7g^5#